2015
DOI: 10.48550/arxiv.1506.03806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An axiomatic characterization of the Brownian map

Abstract: The Brownian map is a random sphere-homeomorphic metric measure space obtained by "gluing together" the continuum trees described by the x and y coordinates of the Brownian snake. We present an alternative "breadth-first" construction of the Brownian map, which produces a surface from a certain decorated branching process. It is closely related to the peeling process, the hull process, and the Brownian cactus.Using these ideas, we prove that the Brownian map is the only random sphere-homeomorphic metric measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(58 citation statements)
references
References 41 publications
5
53
0
Order By: Relevance
“…In the same direction, there are close relations between the present article and the recent work of Miller and Sheffield [32,33,34] aiming at proving the equivalence of the Brownian map and Liouville quantum gravity with parameter γ = 8/3. In particular, the paper [32] uses what we call Brownian snake excursions above the minimum to define the notion of a Brownian disk, corresponding to bubbles appearing in the exploration of the Brownian map: See the definition of µ L DISK in Proposition 4.4, and its proof, in [32].…”
supporting
confidence: 68%
“…In the same direction, there are close relations between the present article and the recent work of Miller and Sheffield [32,33,34] aiming at proving the equivalence of the Brownian map and Liouville quantum gravity with parameter γ = 8/3. In particular, the paper [32] uses what we call Brownian snake excursions above the minimum to define the notion of a Brownian disk, corresponding to bubbles appearing in the exploration of the Brownian map: See the definition of µ L DISK in Proposition 4.4, and its proof, in [32].…”
supporting
confidence: 68%
“…It is widely believed or proven in certain cases to provide, after a Riemann conformal map to a given planar domain, the correct conformal structure for the continuum limit of random planar maps, possibly weighted by the partition functions of various statistical models (see, e.g., the ICM reviews [98,47,103]). In the case of usual random planar maps with faces of bounded degrees, the universal metric structure is that of the Brownian map [97,102], which has been recently identified with that directly constructed from Liouville quantum gravity (LQG) [104,105,106,107]. Note also that different mathematical approaches to LQG exist [56,51,108,35], whose equivalence has been recently established [4].…”
Section: Comparison With Nesting In Cle Via Kpzmentioning
confidence: 99%
“…As of now, the geometry of large random planar maps with faces of bounded degrees (e.g., quadrangulations) is fairly well understood, thanks to recent spectacular progress. In particular, their scaling limit is the so called Brownian map [101,96,102,97,104], with its convergence in the Gromov-Hausdorff sense established by Le Gall and Miermont in Refs. [97,102].…”
Section: Introductionmentioning
confidence: 99%
“…In [7], it was shown that the collection of perimeters of the holes observed when slicing Boltzmann triangulations at all heights converges, when properly rescaled, towards a particular self-similar growth-fragmentation. We also mention Theorems 3 and 23 of Le Gall and Riera [27], which show that, when slicing directly the free Brownian disk, the holes' perimeters are described by the same growth-fragmentation as in [6] (see also [32] Section 4). When X starts from a single cell of size 0 that grows indefinitely, the geometrical connection corresponds this time to the holes in a sliced discrete approximation of the Brownian plane.…”
Section: Introductionmentioning
confidence: 91%